Ergonomic Chair to Reduce the Risk of Low Back Pain among Garment Sewing Workers - Sumardiyono Sumardiyono; Fathiyatur Rohmah Fauziah; Warda Yussy Rha (Universitas Muhammadiyah Surakarta, 2025)
Low back pain (LBP) is highly likely to occur among garment workers because of the fact that they are subjected to prolonged periods of inactivity sitting in non-ergonomic chairs. The ergonomic chair intervention can be regarded as effective in terms of decreasing the level of discomfort and enhancing the comfort at work. The objective of this community service activity was to minimize the risk of LBP by providing ergonomic chairs and posture education in the form of anthropometry to the garment workers. The intervention was done with 22 garment workers in May 2025 and the intervention involved the provision of the ergonomic chairs based on the anthropometric data of the workers. To assess the body posture, the Rapid Upper Limb Assessment (RULA) was used and to determine the level of disability caused by LBP, the Oswestry Disability Index (ODI) was used, where the assessments were done immediately and two weeks after the intervention. The results were found to have significantly improved as the RULA score (a 5.36 to 4.14) and LBP score (a 19.73 to 8.09) dropped by 22.8% and 59.0% respectively which indicated an improvement in the working posture and the reduction in musculoskeletal complaints respectively. The ergonomic chair aided in staying in a more upright and natural sitting position thus alleviating pressure on the spine and back muscles. On the whole, the intervention was useful in the prevention of musculoskeletal disorders and enhancing the comfort of workers, which is an effective ergonomic solution to the garment industry.